1988
DOI: 10.1017/s0022149x00011500
|View full text |Cite
|
Sign up to set email alerts
|

Surface carbohydrate changes onOnchocerca lienalislarvae as they develop from microfilariae to the infective third-stage inSimulium ornatum

Abstract: Use was made of seven FITC labelled lectins as tools to investigate the surface ofOnchocerca lienalislarvae as they develop through to the infective third-stage in a natural vector,Simulium ornatum. The lectins were derived fromCanavalia ensiformis(Con A),Lens culinaris(lentil),Triticum vulgaris(wheat germ),Arachis hypogaea(peanut),Helix pomatia, Phaseolus vulgaris(kidney bean) andTetragonolobus purpureus(asparagus pea). Between 70 and 100 living parasites were examined for each developmental stage; i.e. skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…Similar results were reported with developmental stages of O. lienalis in Simulium (Ham et al, 1988 on both melanized mf and developing larval stages suggest that the larvae may be evading host responses through molecular mimicry. However, there is a possibility that the observed differences in surface lectin binding characteristics were due to larval age differences.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were reported with developmental stages of O. lienalis in Simulium (Ham et al, 1988 on both melanized mf and developing larval stages suggest that the larvae may be evading host responses through molecular mimicry. However, there is a possibility that the observed differences in surface lectin binding characteristics were due to larval age differences.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, blood-dwelling mf and fully matured infective larvae showed little or no binding affinity for the lectins tested; apparently the worms response differently in their vertebrate host. Infective stages of O. lienalis obtained from the head also bound less lectins than those from the thorax (Ham et al, 1988). Rao et al (1987c), however, reported that the cuticular surface of L3 of W. bancrofti bound WGA.…”
Section: Resultsmentioning
confidence: 94%
“…Į-tocopherol); it also is associated with alkaline phosphatase and calcium-activated ATPase activities (Araujo et al 1993;Sayers et al 1984;Smith et al 1998). Filarial developmental transitions induce changes in the protein, lipid and carbohydrate composition of the cuticle (Hirzmann 2002;Apfel et al 1992;Ham et al 1988;Lewis et al 1999), and our transcriptome data indicate that mature mf differentially produce transcripts involved in cuticular structure, including two encoding cuticular collagens, one (TC2854) that is highly similar to C. elegans col-34, and the other an uncharacterized B. malayi gene (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is unlikely to be the explanation, because the haemolymph as such is extremely nutritious itself and the killing and clearance of Onchocerca mf occur within a few hours (Lehman et al 1994;Hagen, unpublished observations). Whatever led to improved survival during the short phase of microfilarial migration to the flight muscle of the blackflies must Methyl--d-M, methyl--d-mannopyranoside; N-acetyl-gluc, N-acetyl-d-glucosamine (Ham et al 1988b). Parallel to these developmental changes, the haemolymph lectin composition of the infected blackfly changes also (Smail & Ham 1988).…”
Section: Discussionmentioning
confidence: 99%
“…. We chose these sugars because they were used for assessing the carbohydrate changes on developing larvae of O. lienalis (Ham et al 1988b).…”
Section: Lectin Inhibition With Carbohydratesmentioning
confidence: 99%